Laparoscopic retroperitoneal resection of the duodenal gastrointestinal stromal tumors in neurofibromatosis type 1; Case Report and literature review - Abdullah, Al-Danakh; Mohammed, Safi; Alradhi, Mohammed; Zhu, Xinqing; Yang, Deyong (Frontiers in Surgery, 2022)
Background Neurofibromatosis type 1, also known as NF1, is a disorder that is passed down in an autosomal dominant manner. It manifests in a wide variety of tumors and affects several organ systems. It is expected that those carrying the NF1 gene will develop a rare mesenchymal tumor known as a gastrointestinal stromal tumor (GIST) more than general population . Case report This research discusses a 42-year-old female patient with NF1 who was identified with a duodenal GIST but clinically and radiographically misinterpreted as having a retroperitoneal neurofibroma. She had minimally invasive retroperitoneal laparoscopic surgery to remove the tumor and primary anastomosis of the affected duodenal wall. A spindle cell GIST was entirely excised during surgery, as indicated by the pathologist. As a consequence of dialogue at a multidisciplinary team meeting, the patient was discharged from the hospital on the fourth postoperative day and is presently undergoing regular clinical follow-up. Conclusion: Anatomically problematic sites, such as the duodenal GIST in NF1 patients, can be treated safely with the laparoscopic retroperitoneal approach even when retroperitoneal neoplasia arises from the intrabdominal structure and protrudes into the retroperitoneal region. .